Réponses

2014-09-26T23:31:29+02:00
(x+3)(ax²+bx+c)=x³−4x²−22x−3
ax³+bx²+cx+3ax²+3bx+3c=x³−4x²−22x−3
ax³+(b+3a)x²+(3b+c)x+3c=x³−4x²−22x−3
⇒ax³=x³⇒a=1
⇒(b+3a)x²=-4x²⇒b+3=-4⇒b=-7
⇒(3b+c)x=-22x⇒-21+c=-22⇒c=-1

2014-09-27T00:16:21+02:00

 Bonsoir

Déterminons les valeurs des coefficients réels a, b et c tel que, pour tout x ∈ R

(x+3)(ax²+bx+c) = x³ − 4x² − 22x − 3

Développons
ax³ + bx² + cx + 3ax² + 3bx + 3c
ax³ + (b+3a)x² + (3b+c)x + 3c

a =1
b + 3a = -4

b + 3 = -4

b = -7
3b+c = -22

3(-7) + c = -22

-21 + c = -22

          c = -22 + 21

          c = - 1

donc on a:

(x+3)(x² - 7x - 1) = x^3 - 7x² - x + 3x² - 21x - 3

(x+3)(x² - 7x - 1) = x^3 - 4x² -22x - 3